Urban China through the lens of neoliberalism: Is a conceptual twist enough?. (January 2019) - Zhou, Yu; Lin, George CS; Zhang, Jun
Neoliberalism as a hegemonic global ideology and framework of governance has been the subject of extensive critical analyses in geography and urban studies. Despite the conceptual difficulties involved, a growing number of scholars have attempted to apply this critical discourse to China. In this commentary, we critically interrogate the urban China literature that deploys the neoliberal lens, mostly authored by scholars outside China, and we raise the fundamental question as to whether this discourse can ever capture the central stories or trajectories of China's urban transformation. We examine the interpretations of China's urban land property market, urban inequality and its spatial manifestation, and the emerging urban governmentality – the areas in which neoliberalism has been most often invoked – to highlight the utility and limitations of a neoliberal treatment of China. We argue that the neoliberal representation of China's urban (re)development, with its preoccupation with capital and class interests, is unable to effectively capture the distinctive nature of entanglement of capital, state and society in China, and thus obscures the driving role and the competing rationalities of the authoritarian state, and the rapid reconfiguration of urban society. By citing examples of recent urban China research, we show that the neoliberalism framework, even in its 'variegated' or 'assemblage' versions, tends to trap China's analysis within a frame of reference comfortable to Western researchers, and ultimately hinders the development of diversified, potentially more fruitful inquiries of the urban world.